Detection of scarred and viable myocardium using a new magnetic resonance imaging technique: blood oxygen level dependent (BOLD) MRI. Issue 7 (1st July 2003) - Egred, M; Al-Mohammad, A; Waiter, G D; Redpath, T W; Semple, S K; Norton, M; Welch, A; Walton, S
Abstract : Background: The identification of viable myocardium in patients with impaired left ventricular contraction secondary to coronary heart disease is important clinically as such myocardium is likely to benefit from revascularisation. Blood oxygen level dependent (BOLD) magnetic resonance imaging (MRI) relies on changes in deoxyhaemoglobin concentration under stress for signal generation and could be used for the differentiation between scarred and viable myocardium. Aim: To assess the signal change on BOLD MRI in viable and scarred myocardium as identified by positron emission tomography (PET). Method: 19 patients with impaired left ventricular contraction and at least one akinetic area were enrolled. They underwent rest and dipyridamole stress MRI, using a double breath hold T2* weighted, ECG gated sequence to produce BOLD contrast images, and cine-MRI for wall thickening assessment. Dynamic perfusion and metabolic PET images followed the MRI. Signal change on BOLD MRI and the wall thickening were compared between rest and stress images in hibernating and scarred segments identified by PET on two short axis slices of mid ventricle, with eight segments each. Results: Using PET, 68 segments were identified as hibernating and 42 as scarred. The hibernating segments were found on BOLD MRI to have an average signal change between rest and stress of −9.53%, compared with −2.15% in the scarred segments (p = 0.008). The average wall thickening was 8.7 mm in the hibernating segments compared with 5.9 mm in the scarred segments (p < 0.0001). Conclusions: BOLD MRI with wall thickening may differentiate scarred and viable myocardium and help identify suitable patients for revascularisation. Further larger studies are needed to establish a threshold for detection, sensitivity, and specificity.